THE EFFECT OF EDUCATION USING KIA BOOKS ON PREGNANT WOMEN KNOWLEDGE - Christiana, Elisa; Irmawati; Ariyanti, Ririn (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Background: The trend of maternal mortality in recent years has fluctuated. One way to prevent maternal mortality is to increase the use of KIA books. However, the current KIA books are not being used optimally, so many mothers do not have knowledge about KIA books. Objectives: To determine the effect of education on the use of KIA books on the knowledge of pregnant women at the Daleman Community Health Center in Sampang Regency. Methods: This study used a descriptive-quantitative method, with sampling using total sampling. The population of this study consisted of 17 people with a sample of 23 respondents, using a questionnaire instrument with a Wilcoxon test. Results: The Wilcoxon test showed that the pre-test and post-test values obtained a result of 0.000 with a significance of p (<0.05), which means that the education provided significantly increased the knowledge of pregnant women at the Daleman Community Health Center, Sampang Regency. Conclusion: The results of the study indicate that education on the use of the KIA book influences the improvement of knowledge among pregnant women at the Daleman Community Health Center in Sampang District. Therefore, it is recommended that education on the Mother and Child Health Handbook be conducted regularly and continuously by health workers, and developed using attractive and easy-to-understand media in order to increase awareness and optimal use of the KIA book among pregnant women.